Fish oil reverses the altered glucose transporter, phosphorylation, insulin receptor substrate-1 (IRS-1) protein level and lipid contents in skeletal muscle of sucrose-rich diet fed rats - D'alessandro, Maria Eugenia Guadalupe (2013)
The role and underlying mechanisms by which n−3 polyunsaturated fatty acids (PUFA) prevent/reverse SRD-induced insulin resistance (IR) in the muscle are not completely understood. Therefore, we examined: triglyceride, diacylglycerol, PKCθ, Glut-4, enzymatic hexokinase activity, IRS-1 protein mass level, and fatty acid composition of muscle phospholipids. Rats were fed a SRD during 6 months. Thereafter, half the animals continued with SRD up to 8 months; the other half was fed a SRD in which CO (8% wt/wt) was replaced by FO (7%+1% CO) for 2 months. Results were compared with those obtained in rats fed a control diet (CD). In SRD-fed rats, FO oil normalized/improved lipid storage and PKCθ protein mass level. Effects of insulin were comparable with those of CD-fed rats. FO reversed impaired glucose phosphorylation, IRS-1, and, under insulin stimulation, Glut-4 protein mass level. FO normalized insulin resistance and increased n−3 PUFAs in muscle phospholipids.